Reasons for Reperfusion Failures in Stent-Retriever-Based Thrombectomy: Registry Analysis and Proposal of a Classification System - Kaesmacher, J.; Gralla, J.; Mosimann, P.J.; Zibold, F.; Heldner, M.R.; Piechowiak, E.; Dobrocky, T.; Arnold, M.; Fischer, U.; Mordasini, P. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: In 5%–10% of patients with acute ischemic stroke with an intention to treat with mechanical thrombectomy, no reperfusion can be achieved (Thrombolysis in Cerebral Infarction score = 0/1). Purpose of this analysis was a systematic assessment of underlying reasons for reperfusion failures.MATERIALS AND METHODS: An intention-to-treat single-center cohort (n = 592) was re-evaluated for all patients in whom no reperfusion could be achieved (n = 63). Baseline characteristics of patients were compared between patients with and without reperfusion failures. After qualitative review of all cases with reperfusion failures, a classification system was proposed and relative frequencies were reported. In a second step, occurrence of delayed recanalization at 24 hours after reperfusion failure and dependency on IV-tPA were evaluated.RESULTS: In 63/592 patients with an intention to perform stent-retriever thrombectomy, no reperfusion was achieved (TICI 0/1, 10.6%, 95% CI, 8.2%–13.1%). Older patients (adjusted OR per yr = 1.03; 95% CI, 1.01–1.05) and patients with M2 occlusion (adjusted OR = 3.36; 95% CI, 1.82–6.21) were at higher risk for reperfusion failure. In most cases, no reperfusion was a consequence of technical difficulties (56/63, 88.9%). In one-third of these cases, reperfusion failures were due to the inability to reach the target occlusion (20/63, 31.7%), while “stent-retriever failure” occurred in 39.7% (25/63) of patients. Delayed recanalization was very rare (18.2%), without dependence on IV-tPA pretreatment status.CONCLUSIONS: Reasons for reperfusion failure in stent-retriever thrombectomy are heterogeneous. The failure to establish intracranial or cervical access is almost as common as stent-retriever failure after establishing intracranial access. Systematic reporting standards of reasons may help to further estimate relative frequencies and thereby guide priorities for technical development and scientific effort.